Characterisation Of Agarose Gel As Breast Mimicking Material - Jamil, Munirah (2016)
Breast MRI has become an essential element in breast imaging. A phantom is a mass of materials that are used to investigate the effects of radiation on human. The aims of this study were to fabricate an agarose phantom as breast mimicking material for MRI and to evaluate agarose gel concentration that has a similar SPGR T1 and T2 relaxation times for normal and abnormal breast tissues. The breast mimicking materials consisted of agarose and gelatine mixture as the background material, which mimics the breast tissue. The background solution composed of 30% of agarose solution and 70% of gelatine solution.